Quotes from Press Releases when Jane Tolmach filed for Assembly
This campaign statement outlines Jane Tolmach's priorities in her bid for the 36th Assembly District, emphasizing effective representation for Ventura County. She argues that the county deserves its fair share of state funding for essential services and highlights the need for a four-year state college to reduce educational and financial burdens on local families. Tolmach identifies tax reform as California's most urgent issue, supporting efforts to shift more responsibility to wealthy individuals and corporations while opposing regressive increases in local property taxes. She pledges to be an independent, full-time legislator dedicated solely to representing Ventura County residents without outside business conflicts.